2021
DOI: 10.1016/j.fertnstert.2021.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA fragmentation index and cumulative live birth rate in a cohort of 2,713 couples undergoing assisted reproduction treatment

Abstract: Objective: To study how the choice of the first assisted reproductive technology treatment type affects the cumulative live birth rate (CLBR) in couples with high sperm DNA fragmentation index (DFI). Design: Longitudinal cohort study. Setting: University-affiliated fertility clinic. Patient(s): A total of 2,713 infertile couples who underwent assisted reproductive technology treatment between 2007 and 2017 were included in the study. All in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Sperm DNA integrity is crucial for fertilization and the development of healthy offspring, and more and more studies have confirmed that sperm DNA damage is related to male infertility (Agarwal et al, 2020). Sperm DNA fragmentation index (DFI) can reflect the integrity of sperm DNA, and is used as an important indicator to evaluate semen quality (Malic Voncina et al, 2021;Yan et al, 2022). This study performed the bioinformatics analysis on the transcriptome data of human sperm with high DNA fragmentation and normal DNA fragmentation, and screened out differentially expressed RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm DNA integrity is crucial for fertilization and the development of healthy offspring, and more and more studies have confirmed that sperm DNA damage is related to male infertility (Agarwal et al, 2020). Sperm DNA fragmentation index (DFI) can reflect the integrity of sperm DNA, and is used as an important indicator to evaluate semen quality (Malic Voncina et al, 2021;Yan et al, 2022). This study performed the bioinformatics analysis on the transcriptome data of human sperm with high DNA fragmentation and normal DNA fragmentation, and screened out differentially expressed RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…The current study by Voncina et al (2) attempts to identify, in a patient population routinely screened for DNA fragmentation index (DFI), the impact of a compromised sperm genome on IVF and ICSI outcomes. Although it is well designed and includes a well-proven test, the study is limited by being a cohort study and lacks randomization.…”
mentioning
confidence: 99%
“…Sperm DNA as a carrier of paternal genetic information, plays an important role in fertilization and embryonic development (48). Sperm DFI can reflect the integrity of sperm DNA and is an important indicator to assist in the evaluation of semen quality after the traditional semen analysis (3,4). Oguz et al compared the effects of two commonly used sperm preparation methods (swim-up and gradient technique) on sperm DFI through SCD method, and the result showed that gradient method has no statistically significant reduction in the DNA fragmented sperm rate after preparation as compared to basal rates (49).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm DNA integrity is crucial for fertilization and the development of healthy offspring, and more and more reports emphasize the direct relationship between sperm DNA damage and male infertility (2). Sperm DFI can reflect the integrity of sperm DNA, and is an important indicator to assist in the evaluation of semen quality after the traditional semen analysis (3,4). With the continuous development of science and technology, many new technologies have been applied to the examination of sperm DFI in clinical practice, including the TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) assay, Comet assay, SCSA (sperm chromatin structure assay), SCD (sperm chromatin dispersion) test, etc.…”
Section: Introductionmentioning
confidence: 99%